Bridging the Gap between Self and Other ? Pictorial Representation of Blacks in England in the Middle of the Eighteenth Century - Élisabeth Martichou (Revue LISA)
In the middle of the eighteenth century a shift in the artistic representation of black people became perceptible in England. Several paintings illustrated a new attitude to the question of identity and differences between the races. Gainsborough’s portrait of Ignatius Sancho shows a gentleman as well as a man of feeling, who nevertheless is kept at a distance from the viewer. Wright of Derby’s Two Girls with a Black Servant hints at a possible equality betwen the children while reminding us of the black girl’s current inferior status. In his portrait of Omai Reynolds fuses signs of exotic alterity and classical cultural references. In Singleton Copley’s Watson and the Shark the black man’s heroic status is undermined by suggestions of passivity. Thus otherness was made acceptable by the use of occidental cultural models, sentiment and noble savagery, but difference was never completely erased.